2011
DOI: 10.1002/cssc.201000318
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Metal Nanoparticles Using Amine–Boranes

Abstract: The development of new synthetic strategies to obtain monodisperse metal nanoparticles on large scales is an attractive prospect in the context of sustainability. Recently, amine-boranes, the classical Lewis acid-base adducts, have been employed as reducing agents for the synthesis of metal nanoparticles. They offer several advantages over the traditional reducing agents like the borohydrides; for example, a much better control of the rate of reduction and, hence, the particle size distribution of metal nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 65 publications
0
40
0
Order By: Relevance
“…In this regard, several efficient catalyst systems have been reported involving Ru, Co and Rh NPs [10], Au NPs [11], Cu (airstable), Ag, and Au NPs [4,12] monometallic Au, Ag, Cu, Pd, Ir and bimetallic CuAg and CuAu alloy NPs [13]. Additionally, many transition metal catalysts involving Rh [14e16], Ru [17,18], bimetallic NiPd [19], Ag [20], borane-based catalyst (CoeB, NieB and CueB) [21] have been tested for solutionphase dehydrogenation of amine borane but there is no report concerning the use of dimethylamine-borane by solvent-free approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several efficient catalyst systems have been reported involving Ru, Co and Rh NPs [10], Au NPs [11], Cu (airstable), Ag, and Au NPs [4,12] monometallic Au, Ag, Cu, Pd, Ir and bimetallic CuAg and CuAu alloy NPs [13]. Additionally, many transition metal catalysts involving Rh [14e16], Ru [17,18], bimetallic NiPd [19], Ag [20], borane-based catalyst (CoeB, NieB and CueB) [21] have been tested for solutionphase dehydrogenation of amine borane but there is no report concerning the use of dimethylamine-borane by solvent-free approach.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The hydrolysis of AB [20][21][22][23][24] and thermolysis of AB [25] and its derivative metal amidoboranes (MNH 2 ÀBH 3 ) [26] have been studied widely. [32] AB has been used as the reducing agent to make bimetallic [33,34] and trimetallic [35,36] core-shell NPs, but the reducing ability of MeAB has not been explored widely. [27] The solid-phase thermolysis of MeAB has been studied: [28] Chen showed that by mixing MeAB with poly(methyl acrylate), MeAB could release H 2 at only 90.5 8C (20 8C lower than the temperature required by neat MeAB).…”
Section: Introductionmentioning
confidence: 99%
“…The reducing strength decreases upon increasing the alkyl substitution on nitrogen: H 3 NÀBH 3 > MeNH 2 ÀBH 3 > Me 2 NHÀBH 3 > Me 3 NÀBH 3 . [32] AB has been used as the reducing agent to make bimetallic [33,34] and trimetallic [35,36] core-shell NPs, but the reducing ability of MeAB has not been explored widely. [30,31,37] Herein, we report a facile in situ method for the preparation of graphene-supported trimetallic core-shell Cu@CoNi NPs through a one-step seeding growth route under ambient conditions, using MeAB as the reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of the metal salt in the absence of capping agent would lead to random 3D architectures . In the past, our group and others established that metal nanoparticles could be obtained via reduction of a metal salt using ammonia borane or substituted amine boranes in both solid and solution states . We attempted to carry out the reduction of metal salts using ammonia borane and substituted amine boranes under different experimental conditions in solution state to investigate the morphological evolution of the resultant material.…”
Section: Resultsmentioning
confidence: 99%
“…[22] In the past, our group and others established that metal nanoparticles could be obtained via reduction of a metal salt using ammonia borane or substituted amine boranes in both solid and solution states. [27][28][29][30][31][32][33][34] We attempted to carry out the reduction of metal salts using ammonia borane and substituted amine boranes under different experimental conditions in solution state to investigate the morphological evolution of the resultant material. Herein, we studied the effect of: (a) metal salt to ammonia borane ratio (molar and volume to volume), (b) dielectric constant of the solvent in which the reduction was carried out, (c) temperature of the reaction, (d) counter-anion of the metal salt used, and (e) reducing power of various amine boranes.…”
Section: Resultsmentioning
confidence: 99%